Targeting Imaging Modality in the Diagnosis of Endometriosis: 68Ga-FAPI-04 PET/CT - Hatice Uslu; Hamza A. Kösem; Meryem Hocaoglu; Burak Canıtez; Dilruba Şahin (Clinical Nuclear Medicine, 2026)
Endometriosis is a chronic condition in reproductive-age women, and diagnosis can be delayed for 4–11 years due to nonspecific symptoms and limited imaging. This underscores the need for new methods to overcome these diagnostic challenges. Fibroblast activation protein, strongly expressed in the perilesional stroma of endometriotic lesions, is a promising PET target. We included 8 women who underwent 68 Ga-FAPI-04 PET/CT for cyclic pelvic or extrapelvic pain and solid nodular lesions, later histopathologically confirmed as endometriosis. In these patients, we showed the targeting diagnostic potential of FAPI PET/CT and endometriotic foci with high accuracy compared with other imaging methods.